2021
DOI: 10.3390/ijerph18052422
|View full text |Cite
|
Sign up to set email alerts
|

Australian Experiences of Out-of-Pocket Costs and Financial Burden Following a Cancer Diagnosis: A Systematic Review

Abstract: (1) Background: This systematic review was conducted to identify cancer patient experiences, and the impact of out-of-pocket costs and financial burden in Australia. (2) Methods: A systematic review, following the Preferring Reporting Items for Systematic Reviews and Meta-Analyses, was conducted. Cumulative Index of Nursing and Allied Health Literature and PubMed were searched. The primary outcome was financial burden among cancer patients and their families in Australia. The secondary outcome was out-of-pocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…For example, financial burden was caused by the practical unmet need of a loss of ability to work (McGrath et al, 2012) and the physical unmet need of lymphoedema development after cancer treatment (Philp et al, 2017). A recent systematic review similarly revealed recurrent financial burdens resulting from out-of-pocket expenses related to cancer (Bygrave et al, 2021), despite the existence of Medicare, Australia's universal health insurance scheme. Certain populations of cancer survivors, also identified in the present review, were considered at greater risk of financial burden, including those living in nonmetropolitan regions with limited access to services and those experiencing lymphoedema (Bygrave et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, financial burden was caused by the practical unmet need of a loss of ability to work (McGrath et al, 2012) and the physical unmet need of lymphoedema development after cancer treatment (Philp et al, 2017). A recent systematic review similarly revealed recurrent financial burdens resulting from out-of-pocket expenses related to cancer (Bygrave et al, 2021), despite the existence of Medicare, Australia's universal health insurance scheme. Certain populations of cancer survivors, also identified in the present review, were considered at greater risk of financial burden, including those living in nonmetropolitan regions with limited access to services and those experiencing lymphoedema (Bygrave et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review similarly revealed recurrent financial burdens resulting from out‐of‐pocket expenses related to cancer (Bygrave et al, 2021), despite the existence of Medicare, Australia's universal health insurance scheme. Certain populations of cancer survivors, also identified in the present review, were considered at greater risk of financial burden, including those living in nonmetropolitan regions with limited access to services and those experiencing lymphoedema (Bygrave et al, 2021). Financial burden on cancer survivors can be both direct (e.g., cost of medications) and indirect (e.g., inability to work, car parking fees and travel expenses) causing negative impacts on QoL and mental health (Durber et al, 2021; McLean et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although people living with and beyond cancer in lower-income countries experience higher financial toxicity, cancer patients in the United States appear particularly vulnerable because of uneven insurance coverage leading to high distress, treatments delayed or even personal bankruptcy. [9] In countries with universal health care system coverage such as Canada, [2,10] Australia, [11] France, or UK, [6] a significant proportion of cancer patients experience financial difficulties. The expenses reported in these health care systems are related to various factors (eg, follow-up visits transportation, parking fees, insurance co-payments, medications).…”
Section: Knowing Is Not Enoughmentioning
confidence: 99%
“…Such critical diseases are well characterized by planned cross-regional medical treatment. In addition, malignant neoplasms pose a high disease economic burden, especially for patients in low-income areas, who are also an important group for cross-regional medical care [33][34][35][36][37][38]. Therefore, this study wants to explore the influence of the temporal and spatial characteristics of cross-regional medical treatment on the total medical expenses, medical insurance payments, and individual outof-pocket expenses of patients with malignant tumors in low-income areas under the background of China's current health care policies, providing strong evidence for improving the fairness of medical security for cross-regional medical patients and reducing their direct economic burden of disease.…”
Section: Introductionmentioning
confidence: 99%